Consumo de amido e fibra e a resposta pós-prandial de glicose de cães - Monti, Mariana [UNESP]; Palumbo, Guilherme Roberto [UNESP]; Pinto, Mariana Vieira de Paula [UNESP]; Putarov, Thaila Cristina [UNESP]; Loureiro, Bruna Agy [UNESP]; Gomes, Márcia de Oliveira Sampaio; Pereira, Gener Tadeu [UNESP]; Carciofi, Aulus Cavalieri [UNESP] (FapUNIFESP (SciELO), 2016)
Fibre has been studied to reduce the postprandial glucose response of dogs, but the results are inconsistent. Starch intake, however, was not properly considered in the published studies. The effects of starch and fibre intake on the postprandial glucose response were studied in non-obese adult dogs. Cellulose (CEL), carboxymethylcellulose (CMC), pea fibre (PE) and sugarcane fibre (SCF) were combined to form six diets with starch contents ranging from 33% to 42%: SCF+CEL and PE+CEL diets, both with high insoluble fibre (IF=22%) and low soluble fibre (SF=2.5%) content; SCF+CMC and PE+CMC diets with high SF (SF=4.5%; IF=19%) content; and CMC and CEL diets with low dietary fibre (14%) content. The diets were fed in two amounts, providing an intake of 9.5g or 12.5g of starch (kg0.75)-1 day-1, totaling 12 treatments. Each diet was fed to six dogs conditioned to consume all of the daily food in 10min. Their plasma glucose levels were measured before and during 480min after food intake. Results of fibre and starch intake and their interactions were compared by repeated measures ANOVA and the Tukey test (P<0.05). Fibre intake did not change the glucose postprandial responses (P>0.05). High-dose starch intake, however, induced a higher glycaemia at 180 and 240min after the meal and a greater maximal glycaemia and greater area under the glucose curve (P<0.05). A range in insoluble and soluble fibre intake does not change postprandial glucose response, and the amount of starch intake is a main factor for the postprandial glucose response of healthy non-obese dogs.
Starch and fibre intake and glucose postprandial response of dogs
Keywords: Dietary fibre; Glycaemia; Metabolic response; Metabolisable energy